Relations between BMI, body mass and height, and sports competence among participants of the 2010 winter Olympic Games: does sport metabolic demand differentiate? - Stanula, A.; Roczniok, R.; Gabrys, T.; Szmatlan-Gabrys, U.; Maszczyk, A; Pietraszewski, P. (Perceptual and Motor Skills, 2013)
This study characterizes the athletes participating in the 2010 Winter Olympic Games in terms of body height, body mass and BMI. The studied sample consisted of athletes in the top 20 places of each of 14 sports disciplines (1460 cases). Data on the athletes' age, height, body mass, and sports specialization were obtained from the Olympic Games' official website and from the International Ski Federation. The sampled athletes were grouped according to the predominant type of energy metabolism during competition. The anaerobic-glycolytic disciplines, such as cross-country sprint, figure skating, short track, and speed skating (500, 1000 and 1500 m), were found to have the youngest female athletes: 25.0 yr. (SD = 4.7). In the endurance sports (aerobic and aerobic-anaerobic), the female athletes were the oldest, being respectively 28.6 yr. (SD = 4.9) and 28.1 yr. (SD = 4.5) old. In the speed disciplines (anaerobic-alactic), the female athletes were the tallest (M = 172 cm; SD = 8.3). The male athletes in the anaerobic-alactic sports were the tallest (M = 181.8 cm, SD = 6.7) and those in the anaerobic-glycolytic sports were the shortest (M = 179.2 cm, SD = 6.7). The large differences in body mass among the groups of athletes, which appear to be related to the predominant type of metabolism during competition, show that this parameter is partly correlated with the level of sports competence, but only in disciplines where the athletes need larger muscle mass. The largest average values of BMI were found for males and females in the anaerobic-alactic group.